Efficacy of diced cartilage graft in dorsal augmentation rhinoplasty and comparison with solid block cartilage - Anchan, Shibani Vittal; Naik, Ashok (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The aim of the study is to compare the results of dorsal augmentation rhinoplasty using diced cartilage graft wrapped in temporalis fascia and bare, solid block of cartilage. Methods: This is a prospective study of a group of 25 patients who presented to ENT OPD from January 2011 to January 2016 with saddle nose deformity. All the patients underwent external septorhinoplasty with dorsal augmentation using either diced cartilage wrapped in temporalis fascia or solid piece of cartilage harvested from septum or concha. Results: The patients were followed up for 18 months post-operatively and the results were recorded in terms of patient’s satisfaction. Complications, if any were also recorded. Conclusions: Comparison between the two groups yielded equal success rate with no evidence of graft resorption, infection or extrusion in either of the group.